The gender dimension of social mood in modern Russia: the experience of historical and sociological analysis - Marina Yu. Milivanova (Наука. Культура. Общество, 2024)
Social mood is the most developed phenomenon of sociological theory and practice, the consideration of which is important for assessment and expertise in times of crises and obvious social changes. Social mood is considered as a phenomenon and an integral characteristic of the perception of life in society, the state of the human spiritual world, an integral form of life perception, the dominant of a really functioning social consciousness and behavior. To identify the gender characteristics of social positions, a primary analysis of the data of the All-Russian sociological monitoring "How are you, Russia?" (1992-2022) during the crisis and turning points of three decades of the modern history of Russia was carried out – 1993, 2001, 2008, 2014, 2022, The data of the research institute "Precariat: a new phenomenon in the socio-economic structure of society" are involved (RNF No. 18-18-00024). The empirical basis for the secondary analysis was the data of the All-Russian centers for sociological research, statistical information, and publications in the media in current periods. A comparison of respondents' responses to problems, their prioritization in the opinions of women and men allowed us to identify dominant events, emerging new combinations of crisis phenomena of economic, political, and spiritual orders in the development of Russian society at mega-, meso-, and microlevels. The conclusion is made about the presence of common constants in the social positions of 1993, 2001, 2008, 2014, 2022, the stable reaction of society with the designation of the main problems of high cost of living, crime, social stratification. The situation of gender communities in the periods under review is characterized by an insufficient "safety cushion", alienation from a power resource, differences in assessments of social expectations about a woman's happiness from the point of view of men and women themselves, and the presence of gender-sensitive problems for both women and men.